Conductive composition capable of being initiated by UV and cured at normal temperature and application thereof

By using components such as epoxy modified acrylic resin and epoxy resin in the conductive adhesive film, combined with UV-induced and room temperature curing processes, the problem of difficult curing of conductive adhesive films in the prior art is solved, and the film preparation with high bond strength and conductive properties is achieved, which is suitable for electronic equipment.

CN119662161APending Publication Date: 2025-03-21SINGLETON (CHANGZHOU) MATERIAL TECH CO LTD +1

Patent Information

Application Number
CN202411967150.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-27
Publication Date
2025-03-21

AI Technical Summary

Technical Problem

The prior art is difficult to cure the conductive adhesive film under UV conditions while maintaining high bond strength and conductive properties, and commonly used thermal activation methods are harmful to electronic device components.

Method used

A conductive composition containing epoxy modified acrylic resin, epoxy resin, photoinitiator, curing agent and conductive material is used to prepare a film with initial viscosity, conductivity and high bond strength by UV initiation and curing at room temperature.

Benefits of technology

The conductive adhesive film activated under UV conditions and cured at room temperature has high bond strength and good conductivity, avoiding damage to electronic device components by high temperature activation.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005218632100000061
    Figure BDA0005218632100000061
Patent Text Reader

Abstract

The invention discloses a conductive composition capable of being initiated by UV and cured at normal temperature and application of the conductive composition. The conductive composition comprises epoxy modified acrylic resin, epoxy resin, a photoinitiator, a curing agent and a conductive material, the epoxy modified acrylic resin is prepared from methyl acrylate monomers, butyl acrylate monomers, acrylic acid-2-hydroxyethyl ester monomers and glycidyl methacrylate monomers. The preparation method of the adhesive film comprises the following steps: uniformly mixing the conductive composition, the silane coupling agent, the leveling wetting agent and the stabilizer, coating and drying to obtain the adhesive film. The adhesive film prepared by the invention has the advantages of good initial adhesion, strong conductivity, capability of being activated under a UV condition and accelerated curing at room temperature or medium and low temperature, high bonding strength after curing and the like, and can be effectively applied to electronic equipment.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of adhesives, and in particular relates to a conductive composition that can be initiated by UV and cured at room temperature and an application thereof. Background Art

[0002] Electronic devices are often bonded to substrates with adhesives. With the development of the industry, there are many types of optional substrates, such as polycarbonate, alumina, metal, glass, etc. In order to improve the good bonding between substrates, the structural adhesive is often heated to a certain temperature to enhance the bonding performance. The reason is that low-temperature cured heat-reactive adhesives usually show low glass transition temperatures (low Tg), and low glass transition temperature adhesives show poor performance reliability when used as structural adhesives, while higher glass transition temperature adhesives often show good performance reliability when used as structural adhesives. Therefore, in order to obtain a high glass transition temperature (high Tg) cured composition for heat-reactive adhesives, curing is usually initiated at high temperatures, and the temperature will exceed 100°C. The industry generally determines the temperature as follows: high temperature, greater than 140°C; medium temperature, 80-120°C; low temperature, room temperature to 80°C. However, most components in electronic devices are sensitive to heat and heating processes. The temperature rise above 100°C will cause the components to soften or melt, damage the function of the components, and cause equipment damage.

[0003] In order to achieve the needs of fine circuit connection and packaging, such as liquid crystal glass and flexible circuits, flexible circuits and rigid circuit boards, integrated circuits and flexible circuits, there is a need for low-temperature activation and high bonding strength, while also requiring certain conductive properties. After the curing bonding process, the XY plane direction is insulated while the Z vertical direction is conductive.

[0004] In the prior art, the films currently using UV curing systems (anionic / cationic initiation systems or free radical initiation systems) are all transparent films, which can be cured after being activated by UV light source, but the light transmittance of the film disappears after adding conductive powder, and UV activation curing cannot be achieved; or heat-activated conductive films are used, although conductive properties can be achieved, but the films generally have no initial adhesion, which increases the difficulty of positioning during the process, and generally require high-temperature hot pressing activation, which increases the cost of the process; or acrylic conductive adhesives are used, although they have initial adhesion and can also achieve conductivity, but the bonding strength of the film is low, and the demand for high bonding strength cannot be achieved. Patent CN1260317C discloses a method for manufacturing anisotropic conductive films, and the prepared films have high thermal curing temperature and high resistance, which have great limitations in use. CN104673113A discloses a light-heat dual-curing anisotropic conductive film and a preparation method thereof, and the curing system used is light and heat dual-initiation curing, which cannot achieve room temperature curing, and its contact resistance is 1.5~3Ω, and the conductivity is poor. Patent CN114907796A discloses a UV curable composition and a film and tape containing the composition, which have good initial adhesion before UV curing and strong shear strength after UV curing, but poor conductivity. Patent CN 116536007A discloses a UV curable bio-based composition and a film and tape prepared therefrom, which have good initial adhesion before UV curing and high structural strength and good adhesion after UV curing, but mainly increase the intrinsic flame retardant properties of the tape.

[0005] Therefore, how to provide an adhesive film that has initial adhesion, conductivity, can be activated under UV conditions, can be accelerated to cure at room temperature or medium and low temperatures, and has high bonding strength after curing is an issue that needs to be solved urgently. Summary of the invention

[0006] The main purpose of the present invention is to provide a conductive composition that can be UV-initiated and cured at room temperature and its application, so as to overcome the shortcomings of the prior art.

[0007] In order to achieve the above-mentioned invention object, the technical solution adopted by the present invention includes:

[0008] One aspect of the present invention provides a conductive composition that can be initiated by UV and cured at room temperature, comprising: an epoxy-modified acrylic resin, an epoxy resin, a photoinitiator, a curing agent, and a conductive material; the epoxy-modified acrylic resin is prepared from methyl acrylate, butyl acrylate, 2-hydroxyethyl acrylate, and glycidyl methacrylate monomers.

[0009] Another aspect of the present invention provides an adhesive film, which is obtained by curing the conductive composition that can be UV-triggered and cured at room temperature.

[0010] Another aspect of the present invention provides a method for preparing an adhesive film, comprising: providing the conductive composition that can be UV-triggered and cured at room temperature; uniformly mixing the conductive composition, a silane coupling agent, a leveling wetting agent, and a stabilizer, and obtaining the adhesive film after coating and drying.

[0011] Another aspect of the present invention also provides use of the adhesive film in electronic devices.

[0012] Compared with the prior art, the present invention has at least the following beneficial effects:

[0013] (1) The present invention provides a self-synthesized epoxy-modified acrylic resin, which introduces glycidyl methacrylate to improve the compatibility of the epoxy-modified acrylic resin with the epoxy resin, and is grafted into the curing system when the epoxy main resin is cured. After the product is cured, it can provide a very strong bonding strength.

[0014] (2) The adhesive film of the present invention can be cured at room temperature or heated to accelerate the curing according to the specific usage scenario. The higher the temperature, the faster the curing rate.

[0015] (3) The adhesive film of the present invention can be UV-initiated and cured at room temperature in the presence of a large amount of conductive powder without being transparent. DETAILED DESCRIPTION

[0016] In view of the problems existing in the above-mentioned prior art, the inventors of the present invention have conducted extensive and in-depth research and have provided a conductive composition that can be UV-initiated and cured at room temperature and its application. The conductive composition mainly comprises an epoxy-modified acrylic resin, an epoxy resin, a photoinitiator, a curing agent, and a conductive material. The epoxy-modified acrylic resin is prepared from methyl acrylate, butyl acrylate, 2-hydroxyethyl acrylate, and glycidyl methacrylate monomers.

[0017] The technical solution, its implementation process and principle will be further explained as follows.

[0018] As one aspect of the technical solution of the present invention, a conductive composition that can be UV-initiated and cured at room temperature is provided, comprising: epoxy-modified acrylic resin, epoxy resin, photoinitiator, curing agent, and conductive material; the epoxy-modified acrylic resin is prepared from methyl acrylate, butyl acrylate, 2-hydroxyethyl acrylate, and glycidyl methacrylate monomers.

[0019] In some embodiments, the conductive composition includes: epoxy-modified acrylic resin, epoxy resin, photoinitiator, photosensitizer which may be added or not added, curing agent, thickener which may be added or not added, conductive material;

[0020] The epoxy modified acrylic resin is prepared from methyl acrylate, butyl acrylate, acrylonitrile which may be added or not added, 2-hydroxyethyl acrylate, tetrahydrofuran methacrylate which may be added or not added, phenyl glycidyl ether which may be added or not added, and glycidyl methacrylate monomer.

[0021] In some preferred embodiments, the conductive composition includes the following components calculated in parts by mass: 20-25 parts of epoxy-modified acrylic resin, 32-37 parts of epoxy resin, 1-1.5 parts of photoinitiator, 0-1 part of photosensitizer, 12-18 parts of curing agent, 0-5 parts of thickener, and 15-20 parts of conductive material.

[0022] In some embodiments, the molecular weight of the epoxy-modified acrylic resin is between 40,000 and 200,000.

[0023] In some embodiments, the preparation method of the epoxy-modified acrylic resin includes: obtaining a mixed solution system comprising methyl acrylate, butyl acrylate, acrylonitrile which may be optionally added or not added, tetrahydrofuran methacrylate which may be optionally added or not added, phenyl glycidyl ether which may be optionally added or not added, 2-hydroxyethyl acrylate, glycidyl methacrylate, an initiator and a solvent; dividing the mixed solution system into a first mixed system and a second mixed system, titrating the second mixed system into the first mixed system and reacting at 55 to 70° C. for 3 to 5 hours, and after all the titrations are completed, reacting at 55 to 70° C. for 9 to 11 hours to prepare the epoxy-modified acrylic resin.

[0024] In some preferred embodiments, the preparation method of the epoxy-modified acrylic resin specifically includes: obtaining a mixed solution system comprising methyl acrylate, butyl acrylate, 2-hydroxyethyl acrylate, glycidyl methacrylate, an initiator and a solvent; dividing the mixed solution system into a first mixed system and a second mixed system, titrating the second mixed system into the first mixed system and reacting at 65° C. for 4 hours, and after all the titration is completed, reacting at 65° C. for 12 hours to prepare the epoxy-modified acrylic resin.

[0025] In some preferred embodiments, the initiator includes azobisisobutyronitrile.

[0026] In some preferred embodiments, the solvent comprises ethyl acetate.

[0027] In some preferred embodiments, the raw materials for preparing the epoxy-modified acrylic resin are calculated according to the following components in parts by mass: 65-85 parts of methyl acrylate, 2-10 parts of butyl acrylate, 0-10 parts of acrylonitrile, 1-5 parts of 2-hydroxyethyl acrylate, 15-20 parts of glycidyl methacrylate, 0.3-0.8 parts of initiator and 80-150 parts of solvent.

[0028] In some preferred embodiments, the mass ratio of the first mixed system to the second mixed system is 1:1.5-3.

[0029] In some more preferred embodiments, the mass ratio of the first mixed system to the second mixed system is 1:2.

[0030] In some embodiments, the epoxy resin includes any one or a combination of two or more of bisphenol A epoxy resin, phenolic modified epoxy resin, amino epoxy resin, aliphatic epoxy resin, etc., but is not limited thereto.

[0031] In some embodiments, the photoinitiator includes at least any one of iodonium salt or tetraphenylborate, but is not limited thereto.

[0032] In some preferred embodiments, the iodonium salt includes any one or a combination of two or more of diphenyliodonium chloride, diphenyliodonium hexafluorophosphate, diphenyliodonium hexafluoroantimonate, diphenyliodonium tetrafluoroborate, etc., but is not limited thereto.

[0033] In some embodiments, the photosensitizer includes any one or a combination of two or more of fluorene photosensitizers, fluorenone photosensitizers, anthraquinone photosensitizers, anthrone photosensitizers, fluoranthene photosensitizers, benzyl ketal photosensitizers, etc., but is not limited thereto.

[0034] In some preferred embodiments, the photosensitizer includes 2-isopropylthioxanthone.

[0035] In some embodiments, the curing agent includes a thiol epoxy curing agent, and the thiol epoxy curing agent includes any one or a combination of two or more of trimethylolpropane trimerthioacetate, tetrakis(3-mercaptopropionic acid) ester (PETMP), hexafunctional thiol, etc., but is not limited thereto.

[0036] In some embodiments, the thickener includes any one of fumed silica and cellulose or a combination of both, but is not limited thereto.

[0037] In some embodiments, the conductive material includes a metal material in the form of a sphere, a sheet, or a chain, but is not limited thereto.

[0038] In some preferred embodiments, the metal material includes any one or a combination of two or more of nickel powder, copper powder, silver powder, etc., but is not limited thereto.

[0039] As another aspect of the technical solution of the present invention, an adhesive film is provided, which is obtained by curing the conductive composition that can be UV-triggered and cured at room temperature.

[0040] In some embodiments, the thickness of the adhesive film is 35 μm, which is used as a thickness benchmark in the present invention. The thickness of the adhesive film is different, and the particle size and addition amount of the conductive powder used are different.

[0041] In some embodiments, the vertical resistance of the adhesive film before UV curing is less than 20mΩ, and the vertical resistance after UV curing is less than 100mΩ. Due to the particularity of the UV curing adhesive film, the adhesive film has no pressure during the UV curing process, and the adhesive has fluidity, which will have a certain wrapping effect on the conductive powder, so the vertical resistance of the adhesive film after UV curing will be slightly higher than the vertical resistance before UV curing, but it still has good conductivity.

[0042] In some embodiments, the minimum dynamic shear strength of the adhesive film is greater than 7Mpa. High bonding strength is an important advantage of the adhesive film of the present invention. The shear strength of conventional pressure-sensitive adhesive products can reach about 2Mpa at most, while the adhesive film of the present invention can reach the strength of structural adhesive or structural adhesive after being fully cured, and its minimum dynamic shear strength is greater than 7Mpa, and can generally reach more than 10Mpa in practice. It is difficult for existing general UV cationic system adhesive films to achieve this bonding strength.

[0043] As another aspect of the technical solution of the present invention, a method for preparing an adhesive film is provided, comprising: providing the conductive composition that can be UV-triggered and cured at room temperature; uniformly mixing the conductive composition, a silane coupling agent, a leveling wetting agent, and a stabilizer, and obtaining the adhesive film after coating and drying.

[0044] In some embodiments, the method for preparing the adhesive film specifically includes: evenly mixing 92-97 parts of the conductive composition, 0.3-0.8 parts of a silane coupling agent, 0-0.5 parts of a leveling wetting agent, and 0-5 parts of a stabilizer, by mass, standing to degas, evenly coating and drying to prepare the adhesive film.

[0045] Furthermore, the curing conditions of the adhesive film are: 1) 365nm LED UVA light source, irradiation energy is 4200mJ / cm 2 ; 2) Leave at room temperature for 3 days or bake at 70°C for 3 hours to accelerate curing.

[0046] The reaction mechanism of preparing the adhesive film of the present invention is the free radical polymerization mechanism of acrylic acid.

[0047] In addition, the self-synthesized epoxy modified acrylic resin of the present invention improves the initial viscosity of the formula system by introducing 2-hydroxyethyl acrylate. By introducing glycidyl methacrylate, the side chain of the self-synthesized resin contains epoxy groups, and according to the principle of like dissolves like, the compatibility of the self-synthesized resin and the epoxy resin is improved; and because the side chain of the self-synthesized resin contains epoxy groups, when the epoxy groups in the subsequent epoxy resin are ring-opened and cured, the self-synthesized resin will also open to participate in the curing reaction and be grafted to the entire curing system to form a uniform cured product; the self-synthesized resin also retains the functional groups such as carboxyl and hydroxyl contained in the acrylic resin, which can improve the interface bonding with the adhered object, thereby improving the bonding strength.

[0048] In the surface or shallow layer of the film, the photoinitiator decomposes under light conditions to produce alkaline substances (Lewis bases). As catalysts, the introduced thiol and epoxy resin can accelerate the speed of cross-linking and curing, and the curing rate is increased exponentially. Therefore, the product can achieve UV-induced curing in the presence of a large amount of conductive powder rather than transparent. And the main curing resin is epoxy resin. After curing, the product can provide strong bonding strength, and the dynamic shear strength can reach the strength of structural adhesive or semi-structural adhesive.

[0049] Moreover, the adhesive film system of the present invention can introduce a large amount of conductive materials, and excellent conductivity can be achieved by selecting conductive materials of different particle sizes such as spherical, flaky and chain-shaped materials. Among them, the addition of spherical conductive materials, flaky and chain-shaped conductive materials, can improve the direct connection of spherical conductive materials, thereby reducing resistance. The vertical resistance before UV curing is less than 20mΩ, and the vertical resistance after UV curing is less than 100mΩ. Moreover, the adhesive film of the present invention can be cured at room temperature or heated to accelerate curing according to the specific usage scenario. The higher the temperature, the faster the curing rate.

[0050] As another aspect of the technical solution of the present invention, application of the adhesive film in electronic equipment is provided.

[0051] In order to make the purpose, technical scheme and advantages of the present invention clearer, the present invention is further described in detail below in conjunction with Examples and Comparative Examples. It should be understood that the specific embodiments and comparative examples described herein are only used to explain the present invention and are not intended to limit the present invention. Those skilled in the art will make modifications or equivalent substitutions based on the understanding of the technical scheme of the present invention, without departing from the spirit and scope of the technical scheme of the present invention, and all should be included in the protection scope of the present invention.

[0052] If no specific experimental steps or conditions are specified in the examples, the conventional experimental steps or conditions described in the literature in the art can be used. If no manufacturer is specified for the reagents or instruments used, they can be obtained commercially. The commercial selection of the remaining raw materials and instruments not mentioned is all conventional selection and does not involve the core technical means of the present invention.

[0053] (1) The reagents used in the examples are as follows:

[0054]

[0055] (2) Product performance test:

[0056] The test standard used for dynamic shear strength is ASTM D1002-10;

[0057] The test standard adopted for vertical resistance is ASTM D257.

[0058] Example 1

[0059] (1) Synthesis of epoxy modified acrylic resin:

[0060] According to the mass proportions, 70 parts of methyl acrylate, 10 parts of butyl acrylate, 5 parts of 2-hydroxyethyl acrylate, 15 parts of glycidyl methacrylate, 0.5 parts of azobisisobutyronitrile and 100 parts of ethyl acetate were fully mixed, one third of the mixture was added into a four-necked flask, and the mixture was stirred and reacted in an oil bath at 65°C under the protection of nitrogen, and the remaining two thirds of the mixture was added into the four-necked flask by titration, and the titration time was 4 hours. After all the titration was completed, the reaction was carried out at a constant temperature of 65°C for 4 hours, and the reaction was terminated. The reaction solution was taken out, and the solid content was adjusted to 40% with ethyl acetate solvent to obtain epoxy-modified acrylic resin sample 1.

[0061] (2) Preparation of film:

[0062] 25 parts of epoxy modified acrylic resin synthesized in (1), 13 parts of bisphenol A epoxy resin, 0.6 parts of WPBG-300 photoinitiator, 0.5 parts of photosensitizer ITX, 4.5 parts of cellulose, 50 parts of conductive powder, 0.3 parts of Maitu A-187 silane coupling agent, 0.1 parts of BYK333 leveling wetting agent, 1 part of maleic anhydride stabilizer and an appropriate amount of ethyl acetate solvent were mixed in equal proportions, allowed to stand for degassing, and evenly coated on a release film. The mixture was baked in an oven at 110° C. for 3 minutes. After being completely dried, a lighter release film was applied to obtain a conductive adhesive film with a thickness of 50 μm.

[0063] Curing conditions of the film: 25℃ / 50%RH environment, irradiation with 365nm LED light source 70mW power for 60 seconds, irradiation energy 4200mJ / cm 2Then put it into a 70℃ oven for accelerated curing for 3 hours, and it is completely cured after being taken out. The product performance results of the obtained film are shown in Table 1.

[0064] Example 2

[0065] (1) Synthesis of epoxy-modified acrylic resin: The basic operation is the same as in Example 1, except that 65 parts of methyl acrylate, 10 parts of butyl acrylate, 5 parts of 2-hydroxyethyl acrylate, 20 parts of glycidyl methacrylate, 0.5 parts of azobisisobutyronitrile and 100 parts of ethyl acetate are used to obtain epoxy-modified acrylic resin sample 2;

[0066] (2) Preparation of adhesive film: Other basic operations are the same as those in Example 1, except that the epoxy-modified acrylic resin used is epoxy-modified acrylic resin sample 2. The product performance results of the obtained adhesive film are shown in Table 1.

[0067] Comparative Example 1

[0068] (2) Preparation of adhesive film: Other basic operations were the same as in Example 1, except that no epoxy-modified acrylic resin was added. The product performance results of the obtained adhesive film are shown in Table 1.

[0069] Comparative Example 2

[0070] (2) Preparation of adhesive film: Other basic operations were the same as in Example 1, except that no epoxy resin was added. The product performance results of the obtained adhesive film are shown in Table 1.

[0071] Comparative Example 3

[0072] (2) Preparation of adhesive film: Other basic operations were the same as in Example 1, except that no photoinitiator was added. The product performance results of the obtained adhesive film are shown in Table 1.

[0073] Comparative Example 4

[0074] (2) Preparation of adhesive film: Other basic operations were the same as in Example 1, except that no curing agent was added. The product performance results of the obtained adhesive film are shown in Table 1.

[0075] Comparative Example 5

[0076] (2) Preparation of adhesive film: Other basic operations are the same as those in Example 1, except that no conductive powder is added. The product performance results of the obtained adhesive film are shown in Table 1.

[0077] Comparative Example 6

[0078] (1) Synthesis of epoxy-modified acrylic resin: The basic operation is the same as that in Example 1, except that 85 parts of methyl acrylate, 10 parts of butyl acrylate, 5 parts of 2-hydroxyethyl acrylate, 0 parts of glycidyl methacrylate, 0.5 parts of azobisisobutyronitrile and 100 parts of ethyl acetate are used to obtain epoxy-modified acrylic resin sample 4.

[0079] (2) Preparation of adhesive film: Other basic operations are the same as those in Example 1, except that the epoxy-modified acrylic resin used is epoxy-modified acrylic resin sample 4. The product performance results of the obtained adhesive film are shown in Table 1.

[0080] Comparative Example 7

[0081] (1) Synthesis of epoxy-modified acrylic resin: The basic operation is the same as in Example 1, except that 75 parts of methyl acrylate, 10 parts of butyl acrylate, 15 parts of glycidyl methacrylate, 0.5 parts of azobisisobutyronitrile and 100 parts of ethyl acetate are used to obtain epoxy-modified acrylic resin sample 5;

[0082] (2) Preparation of adhesive film: Other basic operations are the same as those in Example 1, except that the epoxy-modified acrylic resin used is epoxy-modified acrylic resin sample 5. The product performance results of the obtained adhesive film are shown in Table 1.

[0083] Comparative Example 8

[0084] (1) Synthesis of epoxy-modified acrylic resin: The basic operation is the same as in Example 1, except that 70 parts of methyl acrylate, 10 parts of acrylonitrile, 5 parts of 2-hydroxyethyl acrylate, 15 parts of glycidyl methacrylate, 0.5 parts of azobisisobutyronitrile and 100 parts of ethyl acetate are used to obtain epoxy-modified acrylic resin sample 3;

[0085] (2) Preparation of adhesive film: Other basic operations are the same as those in Example 1, except that the epoxy-modified acrylic resin used is epoxy-modified acrylic resin sample 3. The product performance results of the obtained adhesive film are shown in Table 1.

[0086] Table 1 Product performance data of the films obtained in Examples 1-2 and Comparative Examples 1-8

[0087] Dynamic shear strength(Mpa) Vertical resistance (mΩ) Example 1 7.5 71 Example 2 6.1 68 Comparative Example 1 / / Comparative Example 2 4.3 62 Comparative Example 3 / / Comparative Example 4 / / Comparative Example 5 18 infinity Comparative Example 6 0 / Comparative Example 7 4.5 73 Comparative Example 8 6.7 75

[0088] In Example 1, the obtained adhesive film is the best solution of the present invention, and the obtained adhesive film has high strength and good conductivity.

[0089] In Example 2, since the amount of glycidyl methacrylate added in the epoxy-modified acrylic resin component is too high, the resulting adhesive film is harder, which affects the wettability with the adhered object, and the bonding performance is slightly reduced.

[0090] No epoxy-modified acrylic resin was added in Comparative Example 1. The film-forming property of the obtained film was too poor and the film was too brittle to be tested.

[0091] In Comparative Example 2, no epoxy resin is added, but the synthesized epoxy-modified acrylic resin contains epoxy functional groups. The resulting film can be cured, but its performance is inferior to that of the film with epoxy resin added.

[0092] In Comparative Example 3, no photoinitiator was added, and the obtained film product could not be cured.

[0093] In Comparative Example 4, no curing agent was added, and the obtained film product could not be cured.

[0094] In comparative example 5, no conductive powder was added, and the resulting adhesive film had a higher bonding force without the addition of conductive powder, but lost its conductive properties.

[0095] In Comparative Example 6, glycidyl methacrylate was not added to the synthesized epoxy-modified acrylic resin, resulting in incompatibility between the synthesized epoxy-modified acrylic resin and other components of the adhesive film.

[0096] In Comparative Example 7, 2-hydroxyethyl acrylate was not added to the synthesized epoxy-modified acrylic resin, resulting in reduced initial adhesion of the resulting adhesive film product and reduced wettability with the adhered object, affecting the final bonding performance.

[0097] In Comparative Example 8, since acrylonitrile is introduced into the synthetic epoxy-modified acrylic resin, the modulus of the adhesive film is increased, resulting in a harder product and reduced bonding performance with the adhered object.

[0098] In summary, the adhesive film prepared by the present invention has the advantages of good initial adhesion, strong conductivity, activation under UV conditions, accelerated curing at room temperature or medium and low temperatures, and high bonding strength after curing, and can be effectively used in electronic devices.

[0099] The various aspects, embodiments, features and examples of the present invention should be considered as illustrative in all aspects and are not intended to limit the present invention, the scope of the present invention is defined only by the claims. Other embodiments, modifications and uses will be apparent to those skilled in the art without departing from the spirit and scope of the claimed invention.

[0100] In addition, the inventors of this case also referred to the aforementioned embodiments and conducted experiments with other raw materials, process operations, and process conditions described in this specification, and obtained relatively ideal results.

[0101] Although the present invention has been described with reference to illustrative embodiments, it will be appreciated by those skilled in the art that various other changes, omissions and / or additions may be made without departing from the spirit and scope of the present invention and that the elements of the embodiments may be replaced by substantial equivalents. In addition, many modifications may be made without departing from the scope of the present invention to adapt specific circumstances or materials to the teachings of the present invention. Therefore, it is not intended herein to limit the present invention to the disclosed specific embodiments for performing the present invention, but it is intended that the present invention will include all embodiments within the scope of the appended claims. In addition, unless specifically stated, any use of the terms first, second, etc. does not indicate any order or importance, but rather uses the terms first, second, etc. to distinguish one element from another.

Claims

1. A conductive composition that can be UV-initiated and cured at room temperature, characterized in that: include: Epoxy modified acrylic resin, epoxy resin, photoinitiator, curing agent, conductive material; The epoxy modified acrylic resin is prepared from methyl acrylate, butyl acrylate, 2-hydroxyethyl acrylate and glycidyl methacrylate monomers.

2. The conductive composition according to claim 1, characterized in that The conductive composition comprises: epoxy-modified acrylic resin, epoxy resin, photoinitiator, photosensitizer which may be added or not added, curing agent, thickener which may be added or not added, and conductive material; The epoxy modified acrylic resin is prepared from methyl acrylate, butyl acrylate, acrylonitrile which may be added or not added, tetrahydrofuran methacrylate which may be added or not added, phenyl glycidyl ether which may be added or not added, 2-hydroxyethyl acrylate and glycidyl methacrylate monomers.

3. The conductive composition according to claim 2, characterized in that: The conductive composition includes the following components calculated by mass: 20-25 parts of epoxy modified acrylic resin, 32-37 parts of epoxy resin, 1-1.5 parts of photoinitiator, 0-1 part of photosensitizer, 12-18 parts of curing agent, 0-5 parts of thickener, and 15-20 parts of conductive material.

4. The conductive composition according to claim 2, characterized in that: The number average molecular weight of the epoxy modified acrylic resin is 40000 to 200000; And / or, the preparation method of the epoxy-modified acrylic resin comprises: obtaining a mixed solution system comprising methyl acrylate, butyl acrylate, acrylonitrile which may be added or not added, tetrahydrofuran methacrylate which may be added or not added, phenyl glycidyl ether which may be added or not added, 2-hydroxyethyl acrylate, glycidyl methacrylate, an initiator and a solvent; dividing the mixed solution system into a first mixed system and a second mixed system, titrating the second mixed system into the first mixed system and reacting at 55-70° C. for 3-5 hours, and after all the titration is completed, reacting at 55-70° C. for 9-11 hours to prepare the epoxy-modified acrylic resin; Preferably, the initiator comprises azobisisobutyronitrile; Preferably, the solvent comprises ethyl acetate; Preferably, the raw materials for preparing the epoxy-modified acrylic resin are calculated by weight as follows: 65-85 parts of methyl acrylate, 2-10 parts of butyl acrylate, 0-10 parts of acrylonitrile, 1-5 parts of 2-hydroxyethyl acrylate, 15-20 parts of glycidyl methacrylate, 0.3-0.8 parts of initiator and 80-150 parts of solvent; Preferably, the mass ratio of the first mixed system to the second mixed system is 1:1.5-3.

5. The conductive composition according to claim 2, characterized in that: The epoxy resin includes any one or a combination of two or more of bisphenol A epoxy resin, phenolic modified epoxy resin, amino epoxy resin, and aliphatic epoxy resin; And / or, the photoinitiator comprises at least any one of iodonium salt or tetraphenylborate; Preferably, the iodonium salt includes any one of diphenyliodonium chloride, diphenyliodonium hexafluorophosphate, diphenyliodonium hexafluoroantimonate, and diphenyliodonium tetrafluoroborate, or a combination of two or more thereof; And / or, the photosensitizer includes any one or a combination of two or more of fluorene photosensitizers, fluorenone photosensitizers, anthraquinone photosensitizers, anthrone photosensitizers, fluoranthene photosensitizers, and benzyl ketal photosensitizers, preferably 2-isopropylthioxanthone; And / or, the curing agent includes a thiol epoxy curing agent, and the thiol epoxy curing agent includes any one or a combination of two or more of trimethylolpropane trimercaptoacetate, tetrakis(3-mercaptopropionic acid) ester, and hexafunctional thiol; And / or, the thickener includes any one of fumed silica and cellulose or a combination of both; And / or, the conductive material includes a spherical, sheet-shaped or chain-shaped metal material; Preferably, the metal material includes any one of nickel powder, copper powder and silver powder, or a combination of two or more thereof.

6. A film, characterized in that: The conductive composition is prepared by curing the conductive composition capable of UV initiation and curing at room temperature as described in any one of claims 1 to 5.

7. The adhesive film according to claim 6, characterized in that: The vertical resistance of the adhesive film before UV curing is less than 20 mΩ, and the vertical resistance after UV curing is less than 100 mΩ; And / or, the dynamic shear strength of the adhesive film is greater than 7 MPa.

8. A method for preparing an adhesive film, characterized in that: include: Provide a conductive composition that can be UV-initiated and cured at room temperature according to any one of claims 1 to 5; The conductive composition, silane coupling agent, leveling wetting agent and stabilizer are mixed evenly, and the adhesive film is obtained after coating and drying.

9. The preparation method according to claim 8, characterized in that: include: By weight, 92-97 parts of the conductive composition, 0.3-0.8 parts of a silane coupling agent, 0-0.5 parts of a leveling wetting agent, and 0-5 parts of a stabilizer are mixed evenly, allowed to stand for degassing, and evenly coated and dried to prepare the adhesive film.

10. Use of the adhesive film according to any one of claims 6 or 7 in electronic devices.

Citation Information

Patent Citations

  • Photo-thermal dual-curing anisotropic conductive adhesive film and preparation method thereof

    CN104673113A

  • UV curing composition and adhesive film and adhesive tape containing same

    CN114907796A

  • UV-curable bio-based composition and adhesive film and adhesive tape prepared from UV-curable bio-based composition

    CN116536007A

  • Preparation process of anisotropic conductive coating

    CN1260317C

Cited By

  • UV semi-structural adhesive, preparation method of UV semi-structural adhesive, UV semi-structural adhesive film and preparation method of UV semi-structural adhesive film

    CN121271458A